NUMERACY ANALYSIS OF CLASS V STUDENTS IN SOLVING MINIMUM COMPETENCY ASSESSMENT TYPE NUMERACY PROBLEMS - Lastri Oktaviani; tatang herman (Universitas Majalengka, 2024)
This research aims to measure and analyze the numeracy abilities of class V students in solving Minimum Competency Assessment (MCA) type numeracy questions. The research design used was descriptive quantitative with a sample of 9 students selected purposively. The instrument used is the MCA type numeracy test which consists of 17 questions covering various numeracy content such as numbers, geometry and measurement, data and near distances, and algebra. The research results showed that 11.11% of students were in the low ability category, 55.56% in the medium category, and 33.33% in the high category. The reliability test was measured with a Cronbach's Alpha value of 0.574, indicating moderate reliability. The question with the highest corrected item-total correlation is question number 9 (0.762), while question number 2 has the lowest correlation (-0.283). These findings show that the majority of students are in the medium ability category, but there are several questions that need to be evaluated and revised to increase the consistency and validity of testing. Recommendations for improving the quality of learning include evaluating and revising questions, increasing the number of questions, providing additional guidance, and collaborating with parents. With these steps, it is hoped that students' numerical abilities can be improved significantly.